Uji Antagonisme Beberapa Jamur Saprofit dan Endofit dari Tanaman Pisang terhadap Fusarium oxysporum f.sp. cubens di Laboratorium - Menawati Hutabalian; Mukhtar Iskandar Pinem; Syahrial Oemry (Jurnal Agroekoteknologi, 2015)
This research aims to know antagonism of saprophytic and endophytic fungi against Fusarium oxysporum f. sp. cubens in Laboratory. The research was conducted at Plant Disease Laboratory, Agroecotechnology Program Study, Faculty of Agriculture, University of Sumatera Utara Medan from May to September 2014. It was done by using Completely Randomized Design (CRD) non factorial with seventeen treatments and three replications. The results showed all the saprophytic fungi (Gliocladium sp. and Acrostalagmus sp.) and endophytic fungi (Cephalosporium sp,. Pullularia sp., Aspergillus sp., Penicilium sp., Trichoderma sp. and Hormiscium sp.) potential as biological agents to control F. oxysporum f. sp. cubens in vitro. The best results obtained on Pullularia sp. with the ability to inhibit 60.577%. Interactions between saprophytic and endophytic fungi against F. oxysporum f. sp. cubens causing the hyphae of F. oxysporum f. sp. cubens malformations and lysis.Keywords: banana, Fusarium oxysporum f. sp. cubens, saprophytic fungi, endophytic fungi, nnninteraction